The molecular mechanism of macrophage-adipocyte crosstalk in maintaining energy homeostasis - Zhang, Yudie; Zhang, Bin; Sun, Xiaobo (Frontiers in Immunology, 2024)
Interactions between macrophages and adipocytes in adipose tissue are critical for the regulation of energy metabolism and obesity. Macrophage polarization induced by cold or other stimulations can drive metabolic reprogramming of adipocytes, browning, and thermogenesis. Accordingly, investigating the roles of macrophages and adipocytes in the maintenance of energy homeostasis is critical for the development of novel therapeutic approaches specifically targeting macrophages in metabolic disorders such as obesity. Current review outlines macrophage polarization not only regulates the release of central nervous system and inflammatory factors, but controls mitochondrial function, and other factor that induce metabolic reprogramming of adipocytes and maintain energy homeostasis. We also emphasized on how the adipocytes conversely motivate the polarization of macrophage. Exploring the interactions between adipocytes and macrophages may provide new therapeutic strategies for the management of obesity-related metabolic diseases.